Orbital solitary fibrous tumor: Report of two cases and literature review - Schellini, Silvana Artioli [UNESP]; Hoyama, E.; Marques, MEA; Abreu, E. S.; Yamashita, S. (Elsevier B.V., 2003)
Background: Solitary fibrous tumor (SFT) is a rare, benign, and very uncommon lesion in the orbit. Because of its complex and variable clinical and histological appearance the SIFT is often misdiagnosed.Cases: Two new cases of orbital SIFT are reported, one in a man and the other in a woman, both unilateral and in the superomedial orbit.Observations: Clinical and tomographical evaluations were conducted and the lesions were excised. The histological evaluation showed the tumors were composed of spindle-shaped cells within colla.-en bundles and vascular channels. Immunohistochemical staining was positive for CD 34 and negative for S-100 protein.Conclusion: Immunohistochemical study is an important adjuvant in determining the SIFT diagnosis. Long-term follow-up is necessary because of the possibility of SFT recurrence after excision. (C) 2003 Japanese Ophthalmological Society.
Keywords: immunohistochemical study; orbit; solitary fibrous tumor; spindle cell neoplasm